Adsorptive removal of strontium(II) using macroporous poly(AGE-co-EGDMA) beads modified with resorcin[4]arene - Mulani, K.; Patil, V.; Chavan, N.; Donde, K. (Bulletin of Materials Science, 2019)
Adsorption behaviour of strontium(II) on macroporous poly(allyl glycidyl methacrylate-co-ethylene glycol dimethacrylate) [poly(AGE-co-EGDMA)] beads modified with resorcin[4]arene was studied using macroporous cross-linked [poly(AGE-co-EGDMA)] beads. The macroporous crosslinked [poly(AGE-co-EGDMA)] beads were synthesized by suspension polymerization techniques, followed by functionalization with amino derivatives of resorcin[4]arene. The poly(AGE-co-EGDMA) beads were characterized by FTIR, 1H and 13C-NMR, elemental analysis and particle-size analysis. The surface morphology of beads was studied by scanning electron microscopy. The functionalized poly(AGE-co-EGDMA) beads were used as adsorbents for strontium removal. The crucial factors including the effect of pH, time, initial concentration of metal ions and adsorbent dose were investigated to optimize the maximum adsorption efficiency of Sr(II). The equilibrium data of strontium(II) ions adsorbed on functionalized poly(AGE-co-EGDMA) beads were analysed by pseudo-first- and pseudo-second-order kinetic models. The pseudo-second-order kinetic model indicated that strontium was adsorbed by chemisorption.
Keywords: Adsorption; AGE-EGDMA beads; resorcin[4]arene; Sr(II)